The True Malcolm X speaks - Bass, Debra D. (Las Vegas, NV : Library Distributors of America, 1993)
A unique portrait of Malcolm X emerges from rare archival materials which document his life and times.
VHS format.
Keywords: X, Malcolm, -- 1925-1965.; African Americans -- Biography; Black Muslims